Health monitoring chair (HeMoniC) using internet of things technology / Muhammad Shafeeq Mohd Mahadi - Mohd Mahadi, Muhammad Shafeeq (Faculty of Computer and Mathematical Sciences, 2018)
Using Internet of Things in health monitoring can improve the hospital/ clinic facilities that is why the health monitoring chair (HeMoniC) is develop. This prototype is to help the medical officer to monitor the patient health in short and fast period of time. Using Raspberry Pi 3 as a master board and Arduino as the slave board, Raspberry Pi 3 act as the server that control and manage transition of data from Arduino to database (Raspberry Pi 3) to Android as the monitor to display the result and the number of Arduino connected. The Arduino manage and control the data that is received from the sensors and send the data to the database (MySQL) in Raspberry Pi 3. In order to develop this project, there are 5 phases that are used which are the requirement gathering, analysis and findings, design, development and testing. In the design phase will be the design of user interface (android apps) and the ERD database and for the development phase will be the development of the mobile apps, Arduino and sensors infrastructure, and communication between Raspberry Pi 3 and Arduino. As the result, based on the observation that are conducted at the Hospital Rehabilitation Cheras with this prototype it can reduce the waiting time for the patient to check for their daily medical check-up and only just one doctor or nurse can manage the check-up with ease as 1-4 patient per 10 minutes to improve the service, can reduce the number of staff that need to work on other tasks. In conclusion, this prototype can help to improve and enhance the hospital facilities and services else well reduce the waiting time for the patients to be checked for their daily medical check-up.